A model of norms decay by agents' actions: Norms disappearance and norms collapse - Hammoud M.; Tang A.Y.C.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Robotics; Norms Collapse; Norms Decay; Norms Disappearance; Short periods; Social norm; Multi agent systems